2011
DOI: 10.1097/mbp.0b013e32834e3ba6
|View full text |Cite
|
Sign up to set email alerts
|

Agreement comparison between home and clinic blood pressure measurements in 200 Chinese participants

Abstract: The present study in 200 Chinese demonstrates that BP is higher (a) at the clinic setting compared with at home and (b) on the first day of initiating home BP monitoring. There is moderate agreement between clinic and home BP in diagnosing hypertension. As home BP measurements may best represent the 'true' BP level in normotensives and hypertensives, its use in clinical practice should be promoted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Home blood pressure measurement is performed at home and is influenced by lifestyle. Taking into account the recommendations of the recent guidelines (Table ), lifestyle of the Chinese people, and the results of studies in China, the recommendations on the frequency and duration of home blood pressure measurement are as follows:
Blood pressure should be measured 2‐3 times consecutively with a 1‐minute interval in the morning and evening, respectively, after 5 minutes' rest in the seated position. In patients with newly diagnosed hypertension, at the early phase of treatment, or treated but uncontrolled hypertension, blood pressure should be measured for a successive 5‐7 days. If blood pressure is well controlled, blood pressure can be measured for at least 1 day per week. Blood pressure should be measured after urination.
…”
Section: Measurement Frequency and Durationmentioning
confidence: 99%
“…Home blood pressure measurement is performed at home and is influenced by lifestyle. Taking into account the recommendations of the recent guidelines (Table ), lifestyle of the Chinese people, and the results of studies in China, the recommendations on the frequency and duration of home blood pressure measurement are as follows:
Blood pressure should be measured 2‐3 times consecutively with a 1‐minute interval in the morning and evening, respectively, after 5 minutes' rest in the seated position. In patients with newly diagnosed hypertension, at the early phase of treatment, or treated but uncontrolled hypertension, blood pressure should be measured for a successive 5‐7 days. If blood pressure is well controlled, blood pressure can be measured for at least 1 day per week. Blood pressure should be measured after urination.
…”
Section: Measurement Frequency and Durationmentioning
confidence: 99%
“…A change in HR is considered the most obvious and clinically significant indicator and outcome of shift in the autonomic nervous system balance. 20,35 Elevated HR occurs due to an increased sympathetic and decreased parasympathetic tone. This altered balance of the autonomic nervous system tone could explain and increase in events with the increased HR.…”
Section: Discussionmentioning
confidence: 99%
“…HR increase is one of the most apparent signs of sympathetic hyperactivity. 19,20 HR was measured by 24-hour Holter ECG monitoring (MARS PC, GE Medical Systems Information Technologies, Wauwatosa, WI, USA) at a time of enrolment of patients into the study and one day after the completion of the course of r. auricularis n. vagi electrical stimulation. VNS = electrical stimulation of the auricular branch of the vagus nerve; HR = heart rate; bpm = beats per minute; SBP = systolic blood pressure; DBP = diastolic blood pressure; FC = functional class; HF = heart failure; AMI = acute myocardial infarction; NS = statistically nonsignificant differences between groups.…”
Section: Assessment Of Hrmentioning
confidence: 99%
“…Upon retest, a comparative study found home reliability was as high as r = 0.91 while office test-retest fell between r = 0.6–0.77 [17]. Home readings tend to be significantly lower than office readings [1820] and correlate more closely with ABP readings [8, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…Over 50% of older outpatients attending their first visit for a cognitive evaluation are estimated to have substantial white coat hypertension [23], which could lead to overestimations of hypertensive severity [18]. Home readings also identify individuals with masked hypertension and prehypertension who are at increased risk for cognitive dysfunction and stroke [8].…”
Section: Introductionmentioning
confidence: 99%